SWOT analysis of Chatgpt and Siri: understanding their role and impact as popular AI tools - Shamala, Palaniappan; Shazlin Arkin, Qatrunnada Atiqah; Chinniah, Muruga; Zainuddin, Noor Azrin (Universiti Teknologi MARA, Johor, 2025)
Artificial intelligence (AI) has become one of the most talked-about topics in technology, and for good reason. In recent years, numerous advancements that once seemed confined to science fiction have started to become a reality. Many view AI as a powerful driver of production, with the potential to unlock new avenues for growth and transform how tasks are carried out across various industries. Essentially, AI refers to the development of machines designed to mimic human intelligence and behaviour. This is achieved by examining human brain patterns and cognitive processes, which in turn leads to the creation of intelligent systems and software.